PENGARUH CURRENT RATIO (CR), NET PROFIT MARGIN (NPM) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2020-2020 - Diki Wahyudi; Afrah Junita; Nasrul Kahfi Lubis (CV. Aksara Global Akademia, 2023)
This study aims to determine the effect of Current Ratio, Net Profit Margin, and Return On Assets on stock prices at Food and Beverage Companies listed on the Indonesian Stock Exchange in 2020-2020. The data analysis method used is multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination. From the data analysis, the regression equation Y = 6.518 + 0.773X1 + 0.519X2 + 0.620X3 is obtained. Current Ratio has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Net Profit Margin has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Return On Assets has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Current Ratio, Net Profit Margin, and Return On Assets simultaneously have a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. From the analysis of the coefficient of determination it is known that the Current Ratio, Net Profit Margin, and Return On Assets affect the stock prices of companies in the food and beverage sector by 72.4%, while the remaining 27.6% is influenced by other variables outside this research model.